The Relationship between Learning Activities and Understanding Levels Employing Digital Learning and Self-Learning Methods - Widayati, Indriyani; Udijono, Ari; Salahuddin, Fakhri Dimas; Ma'rifati, Lu'luil (Jurnal Ilmiah Pendidikan dan Pembelajaran, 2023)
The change in the learning mechanism from face-to-face to distance learning during the COVID-19 pandemic occurred not only in formal schools but also in corporate training, for example, in the electricity office. One of the challenges in implementing distance learning is achieving participant understanding. The understanding of participants in digital education and training can be influenced by several factors, such as their learning activities when learning is carried out online. The purpose of this study was to analyze the relationship between the learning activity variables of the participants and the level of understanding of the training participants using digital learning and self-learning methods in the electricity office. This research is an observational analytic study using the cross-sectional method with a sample of 57 electricity office employees. Collecting research data using a questionnaire distributed through the Google Form platform. The chi-square test was used in the statistical analysis, with a significance level of p 0.05. The results of this study indicate that there is a relationship between the participants' learning activities (p=0.000) and the training participants' understanding of digital learning and self-learning methods in the electricity office. Therefore, efforts to increase participants' learning activities through digital learning and self-learning methods need to be carried out in order to increase participants' understanding and lead to successful teaching and learning activities.